METAL ACCUMULATION BY TYPHA DOMINGUENSIS PERS. FROM A HYGROPHILOUS FOREST FRAGMENT IN BRAZIL - Mendonça, Tehra G.; Figueiredo, Bernardino R. (Geochimica Brasiliensis, 2016)
Hygrophilous forests are riverside formations that are frequently degraded in the most industrialized region of Brazil as a result of increasing interference of agriculture, industry and urbanization. This scenario is typical for the surroundings of the Santa Genebra Forest, Southeastern Brazil, where chemical alterations in soil and natural waters are observed. In the present study samples of cattail (Typha dominguensis Pers.) were collected to check the capability of this native species to act as accumulator of metals as well as to investigate the chemical interactions of plant, soil and water. The water chemical composition was determined by ionic chromatography and ICP-MS in dry and wet seasons whereas the soil samples were analyzed by XRF Spectrometry and the crops by ICP-MS. Surface water was classified as Na-K bicarbonate water for the majority of samples and concentrations of PO43-, Fe and Mn exceeding the limits established by Brazilian regulations were noted. The soil samples yielded elevated concentrations for Ba, Cu and V when compared to regulated reference values. The highest metal contents in plants were found for Ba, Sr, Zn, Cu, V and Pb, rather in the roots, and for Mn in the leaves. Metal enrichment in plant in relation to soil and water attests the efficiency of cattail as phyto-accumulator, in particular for vanadium even at low metal contents in the environment. These results also highlight the role played by this species in recycling elements in the ecosystem to which it belongs.